Next Generation System-Wide Liquidity Stress Testing - Puhr, Claus; Neftci, Salih; Santos, Andre; Schmieder, Christian (Washington, D.C. : International Monetary Fund, 2012)
A framework to run system-wide, balance sheet data-based liquidity stress tests is presented. The liquidity framework includes three elements: (a) a module to simulate the impact of bank run scenarios; (b) a module to assess risks arising from maturity transformation and rollover risks, implemented either in a simplified manner or as a fully-fledged cash flow-based approach; and (c) a framework to link liquidity and solvency risks. The framework also allows the simulation of how banks cope with upcoming regulatory changes (Basel III), and accommodates differences in data availability. A case study shows the impact of a "Lehman" type event for stylized banks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet